Cutaneous angiosarcoma: a current update. Issue 11 (15th September 2017) - Shustef, Elina; Kazlouskaya, Viktoryia; Prieto, Victor G; Ivan, Doina; Aung, Phyu P
Abstract : Cutaneous angiosarcoma (cAS) is a rare malignant neoplasm with variable clinical presentation. Although a distinct vascular tumour, cAS shares many overlapping histopathological features with other vasoformative and epithelioid tumours or 'mimickers'. cAS shows aggressive behaviour and carries a grave prognosis, thus early diagnosis is of paramount importance to achieve the best possible outcomes. Recently, several genetic studies were conducted leading to the identification of novel molecular targets in the treatment of cAS. Herein, we present a comprehensive review of cAS with discussion of its clinical, histopathological and molecular aspects, the differential diagnosis, as well as current therapies including ongoing clinical trials.